2016
DOI: 10.1007/s11892-016-0752-4
|View full text |Cite
|
Sign up to set email alerts
|

Where, How, and When: Positioning Posttranslational Modification Within Type 1 Diabetes Pathogenesis

Abstract: Autoreactive T cells specific for islet autoantigens develop in type 1 diabetes (T1D) by escaping central as well as peripheral tolerance. The current paradigm for development of islet autoimmunity is just beginning to include the contribution of posttranslationally modified (PTM) islet autoantigens, for which the immune system may be ignorant rather than tolerant. As a result, PTM is the latest promising lead in the quest to understand how the break in peripheral tolerance occurs in T1D. However, it is not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 81 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…Diabetes-induced nerve damage is highly diffuse, follows a variable course, and is tightly linked to the extent of metabolic dysfunction and generation of reactive oxygen species (ROS) (Feldman et al, 2017). Recent studies suggest that ROS and oxidative stress regulate key cellular processes via post-translational modifications such as ubiquitination, acetylation, nitrosylation, glycation, and linked b--acetlglucosamin ((O-GlcNAcylation), which have been implicated in late complications of diabetes (McLaughlin et al, 2016;Forbes and Cooper 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes-induced nerve damage is highly diffuse, follows a variable course, and is tightly linked to the extent of metabolic dysfunction and generation of reactive oxygen species (ROS) (Feldman et al, 2017). Recent studies suggest that ROS and oxidative stress regulate key cellular processes via post-translational modifications such as ubiquitination, acetylation, nitrosylation, glycation, and linked b--acetlglucosamin ((O-GlcNAcylation), which have been implicated in late complications of diabetes (McLaughlin et al, 2016;Forbes and Cooper 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes mellitus is caused by an autoimmune mechanism that destroys β‐cells in pancreatic islets, resulting in absolute deficiency in insulin. The detection of auto‐antibodies to islet antigens in serum is one of the key elements in the diagnosis of type 1 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown in e.g. T1D 67,68 , systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and multiple sclerosis (MS) 64,69,70 . Studies have shown that prediabetic NOD mice have antibodies and effector T cells that react against citrullinated GPR78 66 , and additionally, increased T cell reactivity to citrullinated peptides arising from GAD65 was described in T1D subjects 65 .…”
Section: Studies and Modulation Of Self And Allergen-specific T Cellsmentioning
confidence: 86%